Stress Prevalence and associated Factors among Bank Employees in Niamey, Niger - Mikponhoue, Rose; Hinson, Antoine Vikkey; Ismaël, Ali Djibo; Adjobimey, Mênonli; Ayelo, Paul Ahoumenou (International Journal of Occupational Safety and Health, 2022)
Introduction: The difficulties associated with the financial crisis have led to deep restructuring in the banking sector. The consequences are the emergence of stress among employees. The objective of this study was to assess job stress and related factors among bank workers in Niamey. Methods: This was a descriptive and analytical cross-sectional study conducted from 24 February to 23 August 2020 among bank workers in Niamey, Niger. A random draw of one agency per bank from four banks of the city, followed by a thorough recruitment of employees from the four selected agencies, was carried out. Stress was measured using the Karasek and Siegrist model. The data had been analyzed with the Epi info7.2 software. Results: A total of 275 employees had been included. The average age was 38.09 ± 7.1 years. They were 152 men (55.27%), a sex ratio of 1.23. Half (50.55%) were executing agents; 30.91% worked more than 5 days a week. The prevalence of stress was 21.90% and 28%, respectively, according to the Siegrist and Karasek models. Work more than 5 days per week (p=0.0254; OR=2.75), feeling job insecurity (p=0.0047; OR=6.99) with the desire to change jobs (p<0.0041; OR=2.90) were associated with stress. On the other hand, male (p=0.0084; OR=0.42 and feeling satisfied with work (p=0.000; OR=0.10) were protective. Conclusion: The prevalence of stress in the banking sector in Niger is high. Measures to reduce the number of working days; ensuring job stability; to reward employees and support women's work are necessary to reduce stress.